Experimental Survey Of The Effect Of Using Diamotite Lightweight Aggregate And Pvc-Coated Glass Fiber On Structural Lightweight Concrete - Tafti, Alireza Shabanian (The Turkish Online Journal of Design Art and Communication, 2016)
Based on the increasing growth of concrete construction in the current development world, much progress in different scientific fields of concrete industry is occurred and production of structural lightweight concrete is the result of such progress. These concretes are constructed using lightweight and strong aggregates. Using different lightweight aggregates to reduce the weight of structural elements and finally structural light weight against earthquake has been development recently. This study applied ultralightweight diamotite. This lightweight aggregate has volume weight of 260 kg/m3 and from weight aspects, it is the lightest lightweight aggregate in the market. In recent years, using different fibers as construction material reinforcement in concrete industry has received much attention. In this study, spiral glass fiber with PVC coating and mesh texture are used. The Researches showed that glass fiber was harmless due to having a PVC coating. This study has experimental evaluation of the effect of using diamotite lightweight aggregate and glass fibers with PVC coating on structural lightweight concrete. To do this, some experiments are performed on all mixtures of lightweight concrete including water absorption test, compressive strength and unit weight on selected mixture design. Based on the results of mentioned constructed samples, the mentioned lightweight concrete had acceptable results despite the low unit weight compared to the similar samples in the presence of diamotite lightweight aggregate and fibers.
Keywords: Lightweight concrete; Leca; Diamotite; PVC-coated Glass fiber